Derecho a la salud materna de las mujeres ngäbes y buglés en Costa Rica. Mitos, percepciones y discriminación - Solano-Acuña, Ana Sofía (2020)
The present work is the result of a long process of contact with the indigenous ngäbe and buglé population residing in Costa Rica, as well as with those who have been forced to travel to work temporarily in the coffee harvest and the pinch of coffee. fruit. It is important to define as a starting point that the migration of this indigenous people in recent years has disrupted the identity construction of the Costa Rican, who had kept the indigenous presence in the cities of the center of the country in the shadow, displacing these identities to historically peripheral areas and rural. Through these pages I will try to offer readers a historical and social context of what has been the incorporation of the ngäbe and buglé population from the second half of the century XX, I will immediately define some elements of a conceptual and methodological that I consider essential to understand these presences, relationships and negations. I continue to single out the case of indigenous women facing displacement (Panamanians) or the myth of foreigners (Costa Ricans), and how they cope with the experience of pregnancy, childbirth and postpartum in a context of social exclusion. I conclude the reflection by offering an overview of the myths, perceptions and difficulties that underlie health personnel and that seriously hinder the possibility of establishing care spaces free from all forms of gender violence and ethnic discrimination.